Predictors of failure in posterior short segment instrumentation for thoracolumbar burst fractures: a systematic review and meta-analysis - Parisa Javadnia; Yousef Ramazani; Mehdi Moradinazar; Nila Salimi; Soroush Moradi; Ehsan Alimohammadi (Journal of Orthopaedic Surgery and Research)
Abstract Background Posterior short segment instrumentation (PSSI) aims to restore spinal stability following thoracolumbar burst fractures. Its advantages include involving fewer mobile segments and reduced operative time compared to posterior long-segment fixation. However, reports of PSSI failure raise concerns about the factors influencing treatment success. This systematic review and meta-analysis seek to determine the prevalence of PSSI failure and identify preoperative imaging characteristics associated with increased failure risk. Method A comprehensive literature search was conducted across PubMed, Embase, Web of Science, and Scopus, adhering to PRISMA guidelines. Data were meticulously extracted from included studies, focusing on predictors of treatment failure in thoracolumbar burst fractures managed with short-segment instrumentation. Statistical analyses utilized STATA version 14.0, with pooled mean differences (MD) and 95% confidence intervals (CI) calculated under a random-effects model to account for heterogeneity. Both univariate and multivariate meta-regressions examined the influence of relevant variables. Funnel plots, along with Egger’s and Begg’s tests, assessed publication bias, with p-values below 0.05 indicating potential bias. Results The initial search identified 492 records, with 21 studies included in the systematic review and 20 in the meta-analysis after screening. The pooled failure rate was 14% (95% CI: 10–19%). Patients with PSSI failure exhibited higher scores in Load Sharing Classification (LSC), preoperative Cobb’s angle (pre-CA), preoperative vertebral wedge angle (pre-VWA), and preoperative vertebral body compression rate (pre-VBCR). The mean differences were 1.38, 5.9, 3.86, and − 4.29, respectively, with high heterogeneity observed across parameters, except for pre-VWA, which showed moderate heterogeneity. Notably, an LSC greater than seven was associated with an increased risk of failure. Meta-regression analyses revealed a significant inverse relationship between preoperative canal stenosis severity and failure rates, likely due to the modified surgical approach involving decompression in such cases. Conclusion PSSI appears to be a viable treatment option for carefully selected patients with thoracolumbar burst fractures, particularly when preoperative imaging suggests favorable parameters. Further research is warranted to refine predictive criteria and optimize patient selection.